استجابة نباتات الذرة الصفراء (Zea mays L.) للتسميد الفوسفاتي وحركية الفوسفور في بعض الترب السورية (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2017)
أجريت تجربة أصص في البيت البلاستيكي في موقع مشتل جامعة تشرين. تضمنت التجربة ثلاثة ترب متباينة في خواصها الكيميائية: 1- تربة حمراء طينية ثقيلة تتميز بمحتواها العالي من الأكاسيد، 2- تربة بازلتية سلتيةلومية، 3- تربة طينية حمراء تتميز بمحتواها العالي من كربونات الكالسيومالكلية (34.8%). وتضمنت التجربة تسميد فوسفاتي باستخدامسوبر فوسفات مركز (TSP)، وبمعدلات متدرجة (0-20-40-60-80-100-150 و 200 مغP/كغ تربة). زرعت نباتات الذرة الصفراء بمعدل نباتين في الأصيص واستمرت التجربة 48 يوم حيث تم حصاد المجموع الخضري واستخلاص المجموع الجذري وذلك قبل تشكل النورة الزهرية. تم تسجيل الأوزان الجافة لأجزاء النبات وإجراء التحاليل الكيميائية لتقدير الفوسفور في النبات وفي تربة الريزوسفير. اختلف شكل استجابة نبات الذرة الصفراء خلال فترة الدراسة لمعدلاتالتسميد الفوسفاتي بحسب نوع التربة، فكان خطياً في التربتين الحمراء الثقيلة والكلسية الحمراء ومنحنياً في التربة البازلتية، واختلفت سرعة تجاوب النباتات للتسميد الفوسفاتي باختلاف الترب المدروسة ومحتواها الأصلي من الفوسفور. كما أدت معدلات التسميد المتزايدة إلى زيادة متدرجة وخطية في أجزاء الفوسفور المستخلص بالرزن ومستخلص البيكربونات بشكله المتفاعل مع الموليبدات(MRP)، ولكن ليس مع الجزء العضوي لمستخلص البيكربونات. لقد تباينت الكمية المثبتهمن الفوسفور المضاف في الترب الثلاثة تبعاً لمستوى الإضافة، معدل امتصاص الفوسفور من قبل النبات المزروع، وبالخواص الكيميائية المتباينة للتربة. لقد زادت الكمية المثبتهمن الفوسفور المضاف وكانت هذه الزيادة خطية.في حين بلغت قيم الفوسفور الذي تعرض للتثبيت كنسبة مئوية من المضاف في الترب الحمراء والبازلتية والكلسية الحمراء 41.7، 68.5، 66% عند مستوى الإضافة 20 مغP/كغ تربة، وتنخفض هذه النسبة إلى 30.2، 41.9 و59.1 % عند مستوى الإضافة 200 مغP/كغ تربة. A pot exrpriment was conducted in a greenhouse in Tishreen University. The experiment included three soils differ in their chemical properties: 1) heavy clay red soil rich in iron oxides; 2) a silty loam basiltic soil; 3) a heavet clay red soil rich in total calcium carbonate (34.8 %). Treatments include application of different levels of triple super phosphate (TSP, 46 % P2O5) ranged from 0, 20, 40, 60, 80, 100, 150, to 200 mg P/kg soil. Pots were sowned with maize (2 plants/pot) and grown for 48 days. At harvest, plant were hatvested before flowering by cutting shoots and extracting roots which were oven dried and weight were recorded prior to digestion and P determination in shoot and root tissues. Samples of rhizosphere soils from each pot replicate were taken for P fractionation and determination. The response of maize to P application differs at period test according to soil type. The increase in growth was linear with increasing P level of application in theheavy red and calcareous red soils, while was polynomial in basilitic soil. The speed of growth increase in response to P application was influenced by native available P in the soil prior to application. The application of P led to linear increase in resin-P and MRP fraction in the bicarbonate extract, but not the Po fraction of the bicarbonate extract. The quantities of fixed applied P varied according to level of P application, the ratio of P uptake by maize plants, and chemical properties of the soil type. The proportion of applied P that was fixed increased linerarly with increasing level of P application. It constitutes 41.7,68.5 and66% at level of P application (20 mg/kg soil), and decreasing to30.2, 41.9 and 59.1% at level of P application (200 mg/kg soil) for red, basiltic, and calcerous red soils, respectively.